2021
DOI: 10.1177/1753193420987522
|View full text |Cite
|
Sign up to set email alerts
|

Normal ranges for measurements of the scaphoid bone from sagittal computed tomography images

Abstract: This study aimed to determine normal values of three parameters commonly used to determine malunion by investigating intact scaphoids on sagittal computed tomography images from healthy individuals. We analysed 62 normal scaphoids and found the mean height–length ratio, lateral intrascaphoid angle and dorsal cortical angle to be 0.58, 27° and 128°, respectively. These measurements had good-to-excellent, poor-to-moderate and moderate-to-good inter- and intra-rater reliabilities, respectively. This study provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…The H/L ratio median was 0.67 (0.57–0.93) before and 0.66 (0.57–0.76) after reconstruction in the incidence group and slightly higher in the control group with 0.70 (0.55–1.03) and 0.68 (0.55–0.81), respectively. These measurements are in line with a previously published study 8 but did not correlate significantly with postoperative CTS.…”
Section: Resultssupporting
confidence: 92%
“…The H/L ratio median was 0.67 (0.57–0.93) before and 0.66 (0.57–0.76) after reconstruction in the incidence group and slightly higher in the control group with 0.70 (0.55–1.03) and 0.68 (0.55–0.81), respectively. These measurements are in line with a previously published study 8 but did not correlate significantly with postoperative CTS.…”
Section: Resultssupporting
confidence: 92%
“…The similarities in the shape of the scaphoid bone in the two wrists of an individual allows the contralateral scaphoid to be used as a good reference (ten Berg et al, 2015a). The mean H/L ratio of an uninjured scaphoid of 0.61 in our study agrees with the mean ratio of 0.58 to 0.61 reported in previous studies (Guldbrandsen et al, 2021;Ring et al, 2005;ten Berg et al, 2015b). Many of the authors in published literature have considered only the injured scaphoid when assessing a deformity and have used a H/L ratio >0.6 as the common cut-off limit for flexion deformity (Forward et al, 2009;Lee et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…This has not been helped with the variations in study design and outcomes assessments in the published literature, as well as a lack of consensus on the definition of scaphoid flexion deformity and how to measure it in a reliable and reproducible way (Seltser et al., 2020; Xiao et al., 2021). Comparisons of different scaphoid measurements suggest that the height–length (H/L) ratio is the best measurement for flexion deformity (Bain et al., 1998; Forward et al., 2009; Guldbrandsen et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, no consensus on the normal value of LISA has been reached in the literature. [21] Although some studies obtained no satisfactory results in patients treated with NVBG and screw fixation for scaphoid non-unions, recent meta-analyses have shown that, despite a higher union rate and earlier union with the VBG technique, this radiological advantage does not provide any functional benefits. [22,23] Additionally, VBGs are technically more difficult and need more surgical experience.…”
Section: Discussionmentioning
confidence: 99%